The Lasting Effects of Working While in School: A Long-Term Follow-Up - Mery Ferrando; Noemi Katzkowicz; Thomas Le Barbanchon; Diego Ubfal (Institute of Labor Economics (IZA), 2025)
This paper provides the first experimental evidence on the long-term effects of work-study programs, leveraging a randomized lottery design from a national program in Uruguay. Participation leads to a persistent 11 percent increase in formal labor earnings seven years after the program, driven by a 4 percent increase in the monthly probability of being employed and a 6 percent increase in monthly wages. Effects are significantly larger for men, while remaining positive for women. The program is highly cost-effective, outperforming most job training programs and reaching levels comparable to early childhood investments.
Keywords: I21; I26; J13; J24; J31; O15; 330; work-study program; youth employment; school-to-work transition; long-term effects